The effects of rapid weight loss and 3-h recovery on energy expenditure, carbohydrate, and fat oxidation in boxing athletes - Sagayama, H.; Yoshimura, E.; Yamada, Y.; Tanaka, H. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Boxers need to consider energy metabolism during rapid weight loss (RWL) followed by rapid weight regain. We examined the effects of RWL and a 3-h acute weight recovery on energy expenditure, carbohydrate oxidation, and fat oxidation in boxing athletes. METHODS: The analysis was based on the data of seven healthy young male athletes who underwent rapid weight loss followed by acute weight recovery. Energy expenditure was evaluated at three time points: one week prior to the acute weight loss (baseline); after the 1-week weight loss period; after a 3-h acute weight recovery period. This three-component model was used to estimate body composition. Sleeping metabolic rate and diet-induced thermogenesis (DIT) were measured in an indirect calorimetry room over a 17-h period. After an overnight fast, a prescribed meal was provided and the DIT was measured over a 3-h period. This was followed by a three-step treadmill running protocol. RESULTS: Weight loss produced a significant decrease in fat mass, fat free mass, and body mass, with recovery of body mass within 3 h (1.7±0.3 kg). Postprandial carbohydrate oxidation was significantly lower during the recovery period than at baseline, while fat oxidation was higher, although there was no change in the DIT. CONCLUSIONS: RWL, followed by a short-term of acute weight recovery, produces an increase in fat oxidation and a decrease in carbohydrate oxidation, with the increase in fat oxidation being maintained through an overnight sleep period, as well as in the postprandial and exercise periods.